Fourier Transform Infrared Spectroscopy study of polymorphism in propylene-co-1-pentene copolymers: Trigonal form identification. (February 2015) - Arranz-Andrés, J.; de la Orden, M.U.; Martínez Urreaga, J.; Gómez-Elvira, J.M.; Pérez, E.; Cerrada, M.L.
Graphical abstract: Highlights: The trigonal δ form in propylene- co -1-pentene copolymers is identified by FTIR. The real time evolution of IR regularity bands during heating is analyzed. The trigonal form affects the location and intensity of other common regularity bands. Abstract: Several regularity bands of the new trigonal form of iPP are identified in a real time FTIR study on a series of random propylene- co -1-pentene copolymers within a broad 1-pentene composition range. Some of them have been already reported for propylene-1-hexene copolymers. Moreover the coexistence of the different crystalline structures developed by these copolymers have been studied. Analysis of the real time evolution of IR regularity bands during heating of these copolymers confirms that when trigonal polymorph is developed its presence affects either the location or intensity of other common regularity bands. Conventional X-ray experiments at room temperature have been also performed to attain the required information on the different polymorphs existing at those distinct compositions analyzed. Additionally, DSC measurements and real-time variable temperature synchrotron experiments have been carried out to ascertain the phase transformations that take place on heating.